Parametric Optimization of Load Bearing Elements for Composite Wing of an Unmanned Aerial Vehicle - Aung Naing Lin; Tatarnikov Oleg; Aung Phyo Wai (MATEC Web of Conferences, 2021)
This paper describes the optimizing results of structural elements of the composite wing of an unmanned aerial vehicle. The thickness and composite lay-up structure of load-bearing elements and wing skin are determined using the ANSYS software package. The optimal structure is presented using the Pareto set method of the “ideal center” basing on four criteria: minimum mass, deflection, normal stress, and maximum safety factor of the wing. Verification calculations were carried out to determine the safety factor of the load-bearing wing structure using a geometrically nonlinear model in FEMAP software.